Effect of Galleries on Thermal Conditions of Urban Open Areas - Kariminia, Shahab (Environment-Behaviour Proceedings Journal, 2016)
Computer simulations were performed by ENVI-met model along with physical measurements in two urban squares under hot summer conditions in Isfahan, central Iran. Each scenario concentrated on adding or extending galleries in each square. The results confirmed the role of galleries on thermal conditions; however, it was found that the effectiveness of this strategy depends on the square geometry. It presented higher efficiency for the small square with higher H/W ratio. This solution is advisable for smaller squares and when the peripheral parts are frequently used compared to the middle areas. Galleries are most efficient when allowing enough natural ventilation.